SISTEM INFORMASI PENYEWAAN APARTEMEN PAKUBUWONO TERRACE PADA SUN 7 PROPERTY BERBASIS WEB - Kiki Kusumawati; Rizky Amelia Syafira (JURNAL SATYA INFORMATIKA, 2021)
Today the world of property business continues to grow and develop, even in the current pandemic. Especially the property business In the field of housing and apartments still survives. Likewise for entrepreneurs who develop Pakubuwono Terrace apartments where they see market opportunities for apartments in Indonesia, especially in the Jakarta region, increasingly in demand. All towers in this apartment can be owned by the owners or rented. Many prospective tenants are interested in renting a site in this apartment and asking for a website that can be seen to find out the initial information about the apartment in question, but the apartment manager has been providing information to prospective tenants through telephone service and requires prospective tenants to come directly to see the apartment site they want, and sometimes there is a discrepancy in information submitted by the officer on the ground. Based on existing constraints, it is necessary for researchers to develop methods of conveying information that have been running conventionally into digitalization through website creation by using the waterfall method as a method of development. As a result, this web-based apartment rental information system is able to provide information on units rented in Pakubuwono Terrace apartments, and the management can manage apartment unit rentals better.